Responses of early life stages of European abalone (Haliotis tuberculata) to ocean acidification after parental conditioning: Insights from a transgenerational experiment. (November 2022) - Auzoux-Bordenave, Stéphanie; Ledoux, Apolline; Martin, Sophie; Di Poi, Carole; Suquet, Marc; Badou, Aïcha; Gaillard, Fanny; Servili, Arianna; Le Goïc, Nelly; Huchette, Sylvain; Roussel, Sabine
Abstract: CO2 absorption is leading to ocean acidification (OA), which is a matter of major concern for marine calcifying species. This study investigated the effects of simulated OA on the reproduction of European abalone Haliotis tuberculata and the survival of its offspring. Four-year-old abalone were exposed during reproductive season to two relevant OA scenarios, ambient pH (8.0) and low pH (7.7). After five months of exposure, abalone were induced to spawn. The gametes, larvae and juveniles were then exposed for five months to the same pH conditions as their parents. Several biological parameters involved in adult reproduction as well as in larval, post-larval and juvenile fitness were measured. No effects on gametes, fertilisation or larval oxidative stress response were detected. However, developmental abnormalities and significant decreases in shell length and calcification were observed at veliger stages. The expression profile of a GABA A receptor-like gene appeared to be regulated by pH, depending on larval stage. Larval and post-larval survival was not affected by low pH. However, a lower survival and a reduction of growth were recorded in juveniles at pH 7.7. Our results confirm that OA negatively impacts larval and juvenile fitness and suggest the absence of carry-over effects on abalone offspring. This may compromise the survival of abalone populations in the near future. Highlights: Abalone has experienced severe population decline worldwide due to overfishing, disease and climate change. OA effects were evaluated on reproduction and early life stages of H. tuberculata through a transgenerational experiment. No carry-over effects were observed on abalone offspring following parental exposure to OA. Larval and juvenile fitness were affected by a pH decrease of 0.3 unit. Species dispersion and survival may be compromised in the near future, with potential negative consequences for European abalone populations.